2010
DOI: 10.1254/jphs.10156fp
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic Modulation of Absence-Like Seizures in Groggy Rats: a Novel Rat Model of Absence Epilepsy

Abstract: Abstract.To explore the role of the serotonergic system in modulating absence seizures, we examined the effects of 5-HT 1A and 5-HT 2 agonists on the incidence of spike-and-wave discharges (SWD) in Groogy (GRY) rats, a novel rat model of absence-like epilepsy. GRY rats exhibited spontaneous absence-like seizures characterized by the incidence of sudden immobile posture and synchronously-associated SWD. The total duration of SWD in GRY rats was about 300 -400 s/15-min observation period under the control condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…ethosuximide and sodium valproate), but not by phenytoin, which lacks anti-absence activity (24). In the present study, we confirmed the incidence of absence-like seizures in Groggy rats, of which the frequency and duration for absence-like seizures were similar to those reported previously (23,25). Since Groggy rats frequently exhibited absence-like seizures, expression analysis in the present study seems to reflect the Kir levels under an ictal state.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…ethosuximide and sodium valproate), but not by phenytoin, which lacks anti-absence activity (24). In the present study, we confirmed the incidence of absence-like seizures in Groggy rats, of which the frequency and duration for absence-like seizures were similar to those reported previously (23,25). Since Groggy rats frequently exhibited absence-like seizures, expression analysis in the present study seems to reflect the Kir levels under an ictal state.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, in the present study, we performed Western blot analysis for Kir4.1 and Kir5.1 subunit expression using the Groggy rat, a newly developed animal model of absence seizures (23)(24)(25), to clarify the pathophysiological alterations of astrocytic Kir channels in absence seizures. The expressional level of the Kir2.1 subunit was evaluated since Kir2.1 channels are also known to be expressed in astrocytes even at low density (26,27).…”
Section: Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The location and immunocytochemical profile of the two interneuron subtypes linked to SpW here indicate neurons that receive both serotoninergic and nicotinergic excitation (Porter et al, 1999;Férézou et al, 2002), suggesting that the pharmacological models of SpW were selectively targeting these cells. The connection to nicotinic receptors links these cells to a great deal of prior work on specific epilepsy syndromes (Fonck et al, 2005), and a less well precedented link between SpW epilepsies and serotonin neuromodulation (Ohno et al, 2010). However, the seemingly differential role of the two interneuron subtypes studies does not begin to make sense unless their different peptidergic components are taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…However, another experiment showed that acute, but not chronic fluoxetine at higher doses (15-25 mg/kg) increased this threshold in mice [13,14]. Fluoxetine also suppressed tonic hindlimb extension in the rat MES model and inhibited spike-and-wave discharges (SWD) in Groogy rats, a model of absence-like epilepsy [86,87]. Dietary fluoxetine (10 mg/kg for 7 days) reduced seizures in the El mouse model of genetically predisposed/handling-triggered epilepsy [88].…”
Section: Fluoxetinementioning
confidence: 99%